TI_GERICHTE 12.2016.147 vom 27. März 2017 , Riconoscimento ed exequatur di un'ordinanza ingiuntiva ex art. 186 ter CPC-It - TI Tribunale d'appello (2017)
Riconoscimento ed exequatur di un'ordinanza ingiuntiva ex art. 186 ter CPC-It